Evaluating Nepalese Commercial Banks’ Performance from the Eyes of EAGLES Rating - Vaidya, Rashesh (Khwopa Journal, 2023)
The paper aimed to evaluate the performance of the Nepalese commercial banks using the EAGLE rating model developed by Vong (1994) based on the bank's earning ability ratio, assets quality ratio, growth rate, liquidity, and equity to which an acronym as EAGLE. Vong and Song (2015) added the 'S' element afterward under EAGLE, renaming EAGLES. The strategy response quotient (S) shows management's capacity to set deposit and loan rates and to control a bank's interest burden, calculated as non-interest income minus any overhead costs. The paper considered the financial information of all the commercial banks operating in Nepal from 2018-19 to 2020-21. The paper found that the banks with a short history in the Nepalese banking industry with aggressive market expansion were at the top of the position under the EAGLES rating. The paper also found that ranking for return on equity (E) and ranking for non-performing loan ratio (A) and ranking for return on equity (E), and ranking for capital adequacy ratio (E) have a significant relationship while determining the ranking of the commercial banks. Similarly, the paper found that the bank with a better position for all the components of EAGLES was at the top for the government-owned commercial banks, while for joint venture banks, the bank with better loan growth, liquidity position, and capital structure was at the top.